Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fmicb.2021.660050
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Bioinformatics Characterization of Superoxide Dismutases in the Desiccation-Tolerant Cyanobacterium Chroococcidiopsis sp. CCMEE 029

Abstract: A genome-wide investigation of the anhydrobiotic cyanobacterium Chroococcidiopsis sp. CCMEE 029 identified three genes coding superoxide dismutases (SODs) annotated as MnSODs (SodA2.1 and SodA2.2) and Cu/ZnSOD (SodC) as suggested by the presence of metal-binding motifs and conserved sequences. Structural bioinformatics analysis of the retrieved sequences yielded modeled MnSODs and Cu/ZnSOD structures that were fully compatible with their functional role. A signal-peptide bioinformatics prediction identified a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…After 1 week of exposure, three sod genes were over‐expressed. Notably, the expression of the membrane‐bound Mn‐SOD ( sod A 2.1) was higher than that of the cytoplasmic Mn‐SOD and Cu/Zn‐SOD ( sod A 2.2 and sod C), thus suggesting its protective role in the periplasm/thylakoid lumen as had been previously reported in response to desiccation (Napoli et al., 2021). The relevance of the antioxidant defense in the perchlorate resistance was reinforced by the over‐expression of four catalases ( kat E, kat G, Mn CAT 1, and MnCAT 2), with the kat E gene upregulated after 1 h of exposure and throughout the 3 weeks of perchlorate exposure.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…After 1 week of exposure, three sod genes were over‐expressed. Notably, the expression of the membrane‐bound Mn‐SOD ( sod A 2.1) was higher than that of the cytoplasmic Mn‐SOD and Cu/Zn‐SOD ( sod A 2.2 and sod C), thus suggesting its protective role in the periplasm/thylakoid lumen as had been previously reported in response to desiccation (Napoli et al., 2021). The relevance of the antioxidant defense in the perchlorate resistance was reinforced by the over‐expression of four catalases ( kat E, kat G, Mn CAT 1, and MnCAT 2), with the kat E gene upregulated after 1 h of exposure and throughout the 3 weeks of perchlorate exposure.…”
Section: Discussionsupporting
confidence: 55%
“…The gathered evidence suggested that the perchlorate resistance of this cyanobacterium might be a byproduct of its desiccation tolerance. Indeed, the perchlorate exposure triggered the upregulation of the trehalose and sucrose biosynthetic pathways and antioxidant defense system, both known to be over‐expressed during the desiccation response (Fagliarone et al., 2020; Napoli et al., 2021). The gene upregulation observed during the early phase of perchlorate exposure (1 h and 1 week), as well as after 2 and 3 weeks of culturing, provided insights into the responses toward this chaotropic agent, independently from the growth state, as the fold change of each gene transcript in perchlorate‐exposed cells was compared with that in control cells grown without perchlorate for the same amount of time.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most known mechanisms against reactive oxygen species, the superoxide dismutase ( sod ), was also annotated (Suppl. Table 5), specifically, the combination of Fe and Mn SOD, which is the type found in filamentous nonheterocystous cyanobacteria (Napoli et al 2021). Other genes related to oxidative damage protection that were detected are: a methionine sulfoxide reductase ( msrA ), the Mn containing catalase (cat ), the DNA-binding protein ( dps ); and peroxiredoxin ( prx ).…”
Section: Resultsmentioning
confidence: 99%
“…Genes known to be involved in resistance mechanisms against stress (Rajeev et al 2013; Soule et al 2013; Shimura et al 2015; Al-Hosani et al 2015; Kopf et al 2015; Ferreira et al 2016; Sinetova et al 2016; Chrismas et al 2016, 2018; Klicki et al 2018; Shang et al 2019; Pathak et al 2019; Kvíderová et al 2019; Pereira et al 2009, 2019; Chatterjee et al 2020; Mosca et al 2021; Ye et al 2021; Napoli et al 2021) were searched in the generated contig database and classified in the following groups: (i) Production of the EPS matrix, (ii) Photoprotection, (iii) Oxidative stress protection, (iv) DNA repair and (v) Osmotic stress protection. When genes were not found in the database, they were searched manually using tblastn against the ULC029 assembled genome with an e-value threshold of 1e-5 and a score higher than 50 bits (following Pearson et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…As previously shown, cyanobacteria that belong to the genera Leptolyngbya and Chroococcidiopsis are rich in flavonoids (Ijaz and Hasnain, 2016 ). Further, Chroococcidiopsis species have demonstrated the overexpression of genes encoding SODs under oxidative stress induced by desiccation (Napoli et al , 2021 ).…”
Section: Discussionmentioning
confidence: 99%